Speaking up against sexual assault on campus: A discussion on three cases of student-led activism in Asia - Schieder, Chelsea Szendi; Dewi, Sita; Devesa, Bea Patricia; Cade, Misha; Yang, Haewon (Asian journal of women's studies, 2025)
This roundtable puts three scholars of student-led movements against sexual assault at educational institutions in discussion with each other as an introduction to their research articles published in the same issue of this journal. The authors—Sita Dewi, Bea Devesa, and Misha Cade—root recent social movements in their local conditions in Indonesia, the Philippines, and Japan, respectively. The collected pieces are important investigations into the conditions under which sexual violence occurs (and potentially can be disrupted) at schools, particularly universities. This roundtable introduces readers to how each of these emerging researchers came to their topic, the larger context in which they are writing, and the feminist methodologies with which they pursue their research. KCI Citation Count: 0